High compressive strength microcement and preparation method thereof

By pretreating and modifying quartz sand, combined with aminated chitosan and modified POSS curing agent, the application problems of microcement in high load environments are solved, and its compressive strength and flexural strength are significantly improved.

CN119143446BActive Publication Date: 2025-03-14GUANGZHOU YUESIMEI DESIGN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411295058.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-15
Publication Date
2025-03-14
Estimated Expiration
2044-09-15

AI Technical Summary

Technical Problem

The application of existing microcement in high-load environments such as bridges, foundations, and industrial floors is limited by problems such as high construction difficulty, insufficient strength, and prone to cracking.

Method used

By pretreating the quartz sand to increase its specific surface area, the quartz sand is modified using a silica sol, and the surface of the quartz sand is sprayed with aminated chitosan solution to improve its compatibility with the epoxy resin. At the same time, a modified POSS curing agent is used to enhance the strength of the epoxy resin to form microcement with high compressive strength.

Benefits of technology

The compressive strength and flexural strength of microcement are significantly improved, and its application performance in high load environments is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high compressive strength microcement and a preparation method thereof, and relates to the technical field of microcement. The present invention proposes a high compressive strength microcement and a preparation method thereof, wherein the microcement adopts cement as a base material, and adds modified quartz sand, as well as admixtures such as talcum powder and fly ash to form a stable mixture. Then, epoxy resin is added to enhance the viscosity and water resistance of the mixture, and at the same time, its workability and strength are improved by adding additives such as a water reducer and an early strength agent. The present invention uses silica sol to modify quartz sand, and small particles of silica sol play a role of physical filling on quartz sand, thereby improving the microstructure of the microcement and improving the mechanical properties of the microcement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microcement, in particular to high-compressive-strength microcement and a preparation method thereof. Background Art

[0002] Microcement is a fine-grained cement material, usually made from cement, fine aggregate and other additives. Compared with traditional cement, microcement has a finer particle distribution and better fluidity, making it widely used in a variety of construction and restoration projects. Microcement is often used in floor and wall decoration, restoration and reinforcement projects due to its excellent adhesion and durability. Although the microcement currently on the market has a unique decorative effect, it generally has problems such as difficulty in construction, insufficient strength, and easy cracking, which limits the application of microcement in high-load environments such as bridges, foundations, and industrial floors.

[0003] In order to solve the above problems and improve the compressive strength of microcement, the present invention provides a microcement with high compressive strength and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide microcement with high compressive strength and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing microcement with high compressive strength comprises the following steps:

[0007] Step 1: Take the pretreated quartz sand and silica sol, stir evenly, ultrasonically disperse for 30-40 minutes, age for 7-8 hours, dry, and then calcine at 390-400°C for 2-2.5 hours, cool, spray the amino chitosan solution, and dry to obtain modified quartz sand;

[0008] Step 2: Take POSS and toluene, stir evenly, heat to 75-80°C, add n-butylamine, react for 11-13h to obtain POSS solution; take polyetheramine, add POSS solution dropwise, heat to 110-115°C to react for 5-6h, and rotary evaporate to obtain modified POSS curing agent;

[0009] Step 3: Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducer, early strength agent, defoamer, epoxy resin, and deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement.

[0010] More optimally, in step 1, the preparation method of silica sol is: take tetraethyl silicate, deionized water, and anhydrous ethanol, stir for 30-40 minutes, then add ammonia water dropwise, heat to 60-65°C, react for 5-6 hours, and obtain silica sol.

[0011] More optimally, in step one, the preparation method of the amino chitosan solution is: take triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add chitosan, stir evenly, heat and reflux for 4-5 hours, filter, wash, and dry to obtain amino chitosan; take amino chitosan and acetic acid, stir evenly to obtain an amino chitosan solution.

[0012] More optimally, in step one, the preparation method of pretreated quartz sand is: take quartz sand, wash it, and obtain washed quartz sand; take the washed quartz sand and ferric chloride solution, stir evenly, heat to 100°C, react for 5-6h, then heat to 195-200°C and calcine for 2-3h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5-6h, then heat to 195-200°C and calcine for 2-3h, to obtain pretreated quartz sand.

[0013] More optimally, the high compressive strength microcement includes the following ingredients, calculated by weight: 90-100 parts of silicate cement, 125-135 parts of 300-350 mesh modified quartz sand, 12-15 parts of fly ash, 10-12 parts of talc, 2-3 parts of retarder, 0.4-0.6 parts of cellulose ether, 0.4-0.6 parts of water reducer, 0.8-1.2 parts of early strength agent, 1-1.4 parts of defoamer, 30-35 parts of epoxy resin, 100-110 parts of deionized water, and 4-5 parts of modified POSS curing agent.

[0014] More optimally, the defoaming agent is an organosilicon defoaming agent; the early strength agent is urea; and the retarder is sodium citrate.

[0015] More optimally, the mesh size of the quartz sand is 300-350 meshes; the mesh size of the fly ash is 300-325 meshes; and the mesh size of the talc is 400-450 meshes.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention proposes a high compressive strength microcement and a preparation method thereof. The microcement uses cement as a base material, adds modified quartz sand, and admixtures such as talcum powder and fly ash to form a stable mixture. Then, epoxy resin is added to enhance the viscosity and water resistance of the mixture. At the same time, by adding additives such as a water reducer and an early strength agent, its workability and strength are improved.

[0018] 2. The present invention uses ferric chloride solution to pretreat quartz sand, so that the surface of quartz sand is loaded with iron oxide, which increases the specific surface area of ​​quartz sand and allows the surface of quartz sand to load more silica sol. Silica sol is used to modify quartz sand, and small particles of silica sol play a role of physical filling on quartz sand, thereby improving the microstructure of microcement and improving the mechanical properties of microcement. Then, the surface of quartz sand loaded with silica sol is further sprayed with amino chitosan solution, so that the surface of quartz sand is loaded with amino groups. At this time, the quartz sand loaded with amino groups can be better mixed with epoxy resin, which improves the dispersibility of modified quartz sand in the matrix and further improves the mechanical properties of microcement.

[0019] 3. POSS is modified with polyetheramine and used as epoxy resin curing agent to enhance the strength of epoxy resin, thereby enhancing the compressive strength of microcement. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The sources of the substances involved in the present invention are not particularly limited, and exemplary examples include:

[0022] Glycidyl POSS: can be purchased from Forsman Technology Co., Ltd., item number: 9502024; polyetheramine: can be purchased from Shanghai McLean, item number: D230; epoxy resin: model: E51; quartz sand: mesh number: 300-350 mesh; fly ash: mesh number: 300-325 mesh; talcum powder: mesh number: 400-450 mesh; silicate cement: can be purchased from Aalborg Portland (Anqing) Co., Ltd., model: 42.5; water reducer: can be purchased from BASF, model: MELFLUX 4930F; defoamer: silicone defoamer, can be purchased from Jinan Shanhai Chemical Technology Co., Ltd., model: XPJ05; cellulose ether: can be purchased from Hefei Hongrui Biotechnology Co., Ltd., item number: 24.

[0023] Embodiment 1: A method for preparing microcement with high compressive strength, comprising the following steps:

[0024] Step 1: Preparation of pretreated quartz sand:

[0025] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0026] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h to obtain pretreated quartz sand;

[0027] Step 2: Preparation of amino chitosan solution:

[0028] Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 8 g of chitosan, stir evenly, heat under reflux for 4.5 h, filter, wash, and dry to obtain amino chitosan; take 5 g of amino chitosan and 100 mL of acetic acid, stir evenly to obtain an amino chitosan solution;

[0029] Step 3: Preparation of silica sol:

[0030] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 35min, then drop 3g of ammonia water, raise the temperature to 62°C, and react for 5.5h to obtain silica sol;

[0031] Step 4: Preparation of modified quartz sand:

[0032] Take 20g of pretreated quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonication for 35min, age for 7.5h, dry, then calcine at 395℃ for 2.3h, cool, spray 50mL of amino chitosan solution, dry to obtain modified quartz sand;

[0033] Step 5: Preparation of modified POSS curing agent:

[0034] Take 2g POSS and 100mL toluene, stir evenly, heat to 78°C, add 0.35g n-butylamine, react for 12h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 112°C to react for 5.5h, and rotary evaporate to obtain modified POSS curing agent;

[0035] Step 6: Preparation of high compressive strength microcement:

[0036] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0037] The high compressive strength microcement includes the following components, calculated by weight: 95 parts of silicate cement, 130 parts of modified quartz sand, 13 parts of fly ash, 11 parts of talc, 2.5 parts of retarder, 0.5 parts of cellulose ether, 0.5 parts of water reducer, 1.0 parts of early strength agent, 1.2 parts of defoamer, 32 parts of epoxy resin, 105 parts of deionized water, and 4.5 parts of modified POSS curing agent.

[0038] Embodiment 2: A method for preparing microcement with high compressive strength, comprising the following steps:

[0039] Step 1: Preparation of pretreated quartz sand:

[0040] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0041] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 5h, then heat to 195°C and calcine for 2h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5h, then heat to 195°C and calcine for 2h to obtain pretreated quartz sand;

[0042] Step 2: Preparation of amino chitosan solution:

[0043] Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 8 g of chitosan, stir evenly, heat under reflux for 4 h, filter, wash, and dry to obtain amino chitosan; take 5 g of amino chitosan and 100 mL of acetic acid, stir evenly to obtain an amino chitosan solution;

[0044] Step 3: Preparation of silica sol:

[0045] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 30min, then drop 3g of ammonia water, raise the temperature to 60℃, and react for 5h to obtain silica sol;

[0046] Step 4: Preparation of modified quartz sand:

[0047] Take 20g of pretreated quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonication for 30min, age for 7h, dry, then calcine at 390℃ for 2h, cool, spray 50mL of amino chitosan solution, dry to obtain modified quartz sand;

[0048] Step 5: Preparation of modified POSS curing agent:

[0049] Take 2g POSS and 100mL toluene, stir evenly, heat to 75°C, add 0.35g n-butylamine, react for 11h to obtain POSS solution; take 10g polyetheramine, dropwise add POSS solution, heat to 110°C to react for 5h, and rotary evaporate to obtain modified POSS curing agent;

[0050] Step 6: Preparation of high compressive strength microcement:

[0051] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0052] The high compressive strength microcement includes the following components, calculated by weight: 90 parts of silicate cement, 125 parts of modified quartz sand, 12 parts of fly ash, 10 parts of talc, 2 parts of retarder, 0.4 parts of cellulose ether, 0.4 parts of water reducer, 0.8 parts of early strength agent, 1 part of defoamer, 30 parts of epoxy resin, 100 parts of deionized water, and 4 parts of modified POSS curing agent.

[0053] Embodiment 3: A method for preparing microcement with high compressive strength, comprising the following steps:

[0054] Step 1: Preparation of pretreated quartz sand:

[0055] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0056] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 6h, then heat to 200°C and calcine for 3h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 6h, then heat to 200°C and calcine for 3h to obtain pretreated quartz sand;

[0057] Step 2: Preparation of amino chitosan solution:

[0058] Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 8 g of chitosan, stir evenly, heat under reflux for 5 h, filter, wash, and dry to obtain amino chitosan; take 5 g of amino chitosan and 100 mL of acetic acid, stir evenly to obtain an amino chitosan solution;

[0059] Step 3: Preparation of silica sol:

[0060] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 40min, then drop 3g of ammonia water, raise the temperature to 65℃, and react for 6h to obtain silica sol;

[0061] Step 4: Preparation of modified quartz sand:

[0062] Take 20g of pretreated quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonication for 40min, age for 8h, dry, then calcine at 400℃ for 2.5h, cool, spray 50mL of amino chitosan solution, dry to obtain modified quartz sand;

[0063] Step 5: Preparation of modified POSS curing agent:

[0064] Take 2g POSS and 100mL toluene, stir evenly, heat to 80°C, add 0.35g n-butylamine, react for 13h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 115°C to react for 6h, and rotary evaporate to obtain modified POSS curing agent;

[0065] Step 6: Preparation of high compressive strength microcement:

[0066] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0067] The high compressive strength microcement includes the following components, calculated by weight: 100 parts of silicate cement, 135 parts of modified quartz sand, 15 parts of fly ash, 12 parts of talc, 3 parts of retarder, 0.6 parts of cellulose ether, 0.6 parts of water reducer, 1.2 parts of early strength agent, 1.4 parts of defoamer, 35 parts of epoxy resin, 110 parts of deionized water, and 5 parts of modified POSS curing agent.

[0068] Comparative Example 1: The quartz sand is not pretreated with ferric chloride solution, and the rest is the same as Example 1:

[0069] Step 1: Preparation of cleaned quartz sand:

[0070] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0071] Step 2: Preparation of amino chitosan solution:

[0072] Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 8 g of chitosan, stir evenly, heat under reflux for 4.5 h, filter, wash, and dry to obtain amino chitosan; take 5 g of amino chitosan and 100 mL of acetic acid, stir evenly to obtain an amino chitosan solution;

[0073] Step 3: Preparation of silica sol:

[0074] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 35min, then drop 3g of ammonia water, raise the temperature to 62°C, and react for 5.5h to obtain silica sol;

[0075] Step 4: Preparation of modified quartz sand:

[0076] Take 20g of cleaned quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonication for 35min, age for 7.5h, dry, then calcine at 395℃ for 2.3h, cool, spray 50mL of amino chitosan solution, dry to obtain modified quartz sand;

[0077] Step 5: Preparation of modified POSS curing agent:

[0078] Take 2g POSS and 100mL toluene, stir evenly, heat to 78°C, add 0.35g n-butylamine, react for 12h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 112°C to react for 5.5h, and rotary evaporate to obtain modified POSS curing agent;

[0079] Step 6: Preparation of high compressive strength microcement:

[0080] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0081] The high compressive strength microcement includes the following components, calculated by weight: 95 parts of silicate cement, 130 parts of modified quartz sand, 13 parts of fly ash, 11 parts of talc, 2.5 parts of retarder, 0.5 parts of cellulose ether, 0.5 parts of water reducer, 1.0 parts of early strength agent, 1.2 parts of defoamer, 32 parts of epoxy resin, 105 parts of deionized water, and 4.5 parts of modified POSS curing agent.

[0082] Comparative Example 2: The quartz sand is not modified by using silica sol, and the rest is the same as Example 1:

[0083] Step 1: Preparation of pretreated quartz sand:

[0084] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0085] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h to obtain pretreated quartz sand;

[0086] Step 2: Preparation of amino chitosan solution:

[0087] Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 8 g of chitosan, stir evenly, heat under reflux for 4.5 h, filter, wash, and dry to obtain amino chitosan; take 5 g of amino chitosan and 100 mL of acetic acid, stir evenly to obtain an amino chitosan solution;

[0088] Step 3: Preparation of modified quartz sand:

[0089] Take 20 g of pretreated quartz sand, spray 50 mL of amino chitosan solution, and dry to obtain modified quartz sand;

[0090] Step 4: Preparation of modified POSS curing agent:

[0091] Take 2g POSS and 100mL toluene, stir evenly, heat to 78°C, add 0.35g n-butylamine, react for 12h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 112°C to react for 5.5h, and rotary evaporate to obtain modified POSS curing agent;

[0092] Step 5: Preparation of high compressive strength microcement:

[0093] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0094] The high compressive strength microcement includes the following components, calculated by weight: 95 parts of silicate cement, 130 parts of modified quartz sand, 13 parts of fly ash, 11 parts of talc, 2.5 parts of retarder, 0.5 parts of cellulose ether, 0.5 parts of water reducer, 1.0 parts of early strength agent, 1.2 parts of defoamer, 32 parts of epoxy resin, 105 parts of deionized water, and 4.5 parts of modified POSS curing agent.

[0095] Comparative Example 3: The chitosan solution was not subjected to amination treatment, and the rest was the same as in Example 1:

[0096] Step 1: Preparation of pretreated quartz sand:

[0097] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0098] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h to obtain pretreated quartz sand;

[0099] Step 2: Preparation of chitosan solution:

[0100] Take 5 g of chitosan and 100 mL of acetic acid, stir evenly to obtain a chitosan solution;

[0101] Step 3: Preparation of silica sol:

[0102] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 35min, then drop 3g of ammonia water, raise the temperature to 62°C, and react for 5.5h to obtain silica sol;

[0103] Step 4: Preparation of modified quartz sand:

[0104] Take 20g of pretreated quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonication for 35min, age for 7.5h, dry, then calcine at 395℃ for 2.3h, cool, spray 50mL of chitosan solution, dry to obtain modified quartz sand;

[0105] Step 5: Preparation of modified POSS curing agent:

[0106] Take 2g POSS and 100mL toluene, stir evenly, heat to 78°C, add 0.35g n-butylamine, react for 12h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 112°C to react for 5.5h, and rotary evaporate to obtain modified POSS curing agent;

[0107] Step 6: Preparation of high compressive strength microcement:

[0108] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0109] The high compressive strength microcement includes the following components, calculated by weight: 95 parts of silicate cement, 130 parts of modified quartz sand, 13 parts of fly ash, 11 parts of talc, 2.5 parts of retarder, 0.5 parts of cellulose ether, 0.5 parts of water reducer, 1.0 parts of early strength agent, 1.2 parts of defoamer, 32 parts of epoxy resin, 105 parts of deionized water, and 4.5 parts of modified POSS curing agent.

[0110] Comparative Example 4: The amino chitosan solution was not sprayed, and the rest was the same as Example 1:

[0111] Step 1: Preparation of pretreated quartz sand:

[0112] Taking quartz sand, washing it, and obtaining washed quartz sand;

[0113] Take 30g of cleaned quartz sand and 100mL of 2mol / L ferric chloride solution, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5.5h, then heat to 198°C and calcine for 2.5h to obtain pretreated quartz sand;

[0114] Step 2: Preparation of silica sol:

[0115] Take 22g of tetraethyl silicate, 20mL of deionized water, and 200g of anhydrous ethanol, stir for 35min, then drop 3g of ammonia water, raise the temperature to 62°C, and react for 5.5h to obtain silica sol;

[0116] Step 3: Preparation of modified quartz sand:

[0117] Take 20g of pretreated quartz sand and 100mL of silica sol, stir evenly, disperse by ultrasonic for 35min, age for 7.5h, dry, then calcine at 395℃ for 2.3h, and cool to obtain modified quartz sand;

[0118] Step 4: Preparation of modified POSS curing agent:

[0119] Take 2g POSS and 100mL toluene, stir evenly, heat to 78°C, add 0.35g n-butylamine, react for 12h to obtain POSS solution; take 10g polyetheramine, add POSS solution dropwise, heat to 112°C to react for 5.5h, and rotary evaporate to obtain modified POSS curing agent;

[0120] Step 5: Preparation of high compressive strength microcement:

[0121] Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement;

[0122] The high compressive strength microcement includes the following components, calculated by weight: 95 parts of silicate cement, 130 parts of modified quartz sand, 13 parts of fly ash, 11 parts of talc, 2.5 parts of retarder, 0.5 parts of cellulose ether, 0.5 parts of water reducer, 1.0 parts of early strength agent, 1.2 parts of defoamer, 32 parts of epoxy resin, 105 parts of deionized water, and 4.5 parts of modified POSS curing agent.

[0123] experiment:

[0124] The high compressive strength microcement prepared in Examples 1 to 3 was prepared into a 40 mm × 40 mm × 160 mm test piece, cured for 24 h at 20 ° C and 90% relative humidity, then demolded and cured in water for 28 days, and then the performance test was performed. The compressive strength and flexural strength of the test piece were tested with reference to GB / T17671-2021, and the obtained data are as follows:

[0125] Compressive strength / MPa Flexural strength / MPa Example 1 91.7 24.6 Example 2 91.4 24.3 Example 3 91.8 24.7 Comparative Example 1 88.1 22.7 Comparative Example 2 86.8 21.2 Comparative Example 3 89.2 23.4 Comparative Example 4 88.3 22.9

[0126] Conclusion: Comparative Example 1 does not use ferric chloride solution to pretreat quartz sand, the specific surface area of ​​quartz sand is small, the silica sol loaded on the surface of quartz sand is small, and the mechanical properties of microcement are reduced. Comparative Example 2 does not use silica sol to modify quartz sand, and the mechanical properties of microcement are poor. Comparative Example 3 does not perform amino treatment on chitosan solution. At this time, there are fewer amino groups on chitosan, and the compatibility of quartz sand with epoxy resin is slightly poor, and the mechanical properties are reduced. Comparative Example 4 does not spray amino chitosan solution, and the dispersibility of quartz sand in the matrix is ​​poor, and the mechanical properties are not good. Examples 1-3 of the present invention use ferric chloride solution to pretreat quartz sand, so that the surface of quartz sand is loaded with iron oxide, which increases the specific surface area of ​​quartz sand, so that the surface of quartz sand can load more silica sol. Silica sol is used to modify quartz sand, and small particles of silica sol play a role of physical filling on quartz sand, thereby improving the microstructure of microcement and improving the mechanical properties of microcement. In Example 1-3, an amino chitosan solution is sprayed on the surface of quartz sand loaded with silica sol, so that the surface of the quartz sand is loaded with amino groups. At this time, the quartz sand loaded with amino groups can be better mixed with the epoxy resin, thereby improving the dispersibility of the modified quartz sand in the matrix and further improving the mechanical properties of the microcement. At this time, the compressive strength can reach 91 MPa, the flexural strength can reach 24 MPa, and the mechanical properties are excellent.

[0127] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing microcement with high compressive strength, characterized in that: The following steps are involved: Step 1: Take the pretreated quartz sand and silica sol, stir evenly, ultrasonically disperse for 30-40 minutes, age for 7-8 hours, dry, and then calcine at 390-400°C for 2-2.5 hours, cool, spray the amino chitosan solution, and dry to obtain modified quartz sand; Step 2: Take POSS and toluene, stir evenly, heat to 75-80°C, add n-butylamine, react for 11-13h to obtain POSS solution; take polyetheramine, add POSS solution dropwise, heat to 110-115°C to react for 5-6h, and rotary evaporate to obtain modified POSS curing agent; Step 3: Take silicate cement, modified quartz sand, fly ash, talcum powder, retarder, cellulose ether, water reducing agent, early strength agent, defoamer, epoxy resin, and deionized water, stir evenly to obtain a mixture, add modified POSS curing agent, stir evenly to obtain high compressive strength microcement; In step one, the preparation method of pretreated quartz sand is as follows: take quartz sand, wash it, and obtain washed quartz sand; take the washed quartz sand and ferric chloride solution, stir evenly, heat to 100°C, react for 5-6h, then heat to 195-200°C and calcine for 2-3h, cool, add 100mL of 2mol / L ferric chloride solution again, stir evenly, heat to 100°C, react for 5-6h, then heat to 195-200°C and calcine for 2-3h, to obtain pretreated quartz sand.

2. The method for preparing a high compressive strength microcement according to claim 1, characterized in that: In step 1, the preparation method of silica sol is: take tetraethyl silicate, deionized water, and anhydrous ethanol, stir for 30-40 minutes, then add ammonia water dropwise, heat to 60-65° C., react for 5-6 hours, and obtain silica sol.

3. The method for preparing a high compressive strength microcement according to claim 1, characterized in that: In step 1, the preparation method of the amino chitosan solution is as follows: take triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add chitosan, stir evenly, heat and reflux for 4-5 hours, filter, wash, and dry to obtain amino chitosan; take amino chitosan and acetic acid, stir evenly to obtain an amino chitosan solution.

4. The method for preparing a high compressive strength microcement according to claim 1, characterized in that: The high compressive strength microcement comprises the following components, calculated by weight: 90-100 parts of silicate cement, 125-135 parts of 300-350 mesh modified quartz sand, 12-15 parts of fly ash, 10-12 parts of talc, 2-3 parts of retarder, 0.4-0.6 parts of cellulose ether, 0.4-0.6 parts of water reducer, 0.8-1.2 parts of early strength agent, 1-1.4 parts of defoamer, 30-35 parts of epoxy resin, 100-110 parts of deionized water, and 4-5 parts of modified POSS curing agent.

5. The method for preparing a high compressive strength microcement according to claim 4, characterized in that: The defoaming agent is an organosilicon defoaming agent; the early strength agent is urea; and the retarder is sodium citrate.

6. The method for preparing a high compressive strength microcement according to claim 4, characterized in that: The mesh number of the quartz sand is 300-350 meshes; the mesh number of the fly ash is 300-325 meshes; and the mesh number of the talcum powder is 400-450 meshes.

7. The high compressive strength microcement prepared according to the method for preparing high compressive strength microcement according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Manufacturing method for dry hanging rammed wallboard

    CN105731927A

  • Grout material for road reinforcement and preparation method thereof

    CN108455936A